2014
DOI: 10.1021/cm503132e
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of GdBaCo2O5+δ (δ = 7/18) at Elevated Temperatures

Abstract: The structural chemistry of the double-layered perovskite-type gadolinium barium cobaltate, GdBaCo2O5+δ (0 < δ < 1/2), is not well-known, in comparison to the representative end-member phases α at δ = 0 and β at δ = 1/2. This study unveils the structural evolution of the room-temperature stable phase γ at δ = 7/18, using in situ single-crystal X-ray diffraction at elevated temperatures and electron microscopy. The γ phase is essentially charge-ordered with Co3+ and Co2+ in a ratio of 8:1 and is incommensuratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Tsvetkov et al [ 36 ] reported a similar behavior for PrBaCo 2 O 5+δ where a transition from P4/mmm to Pmmm was observed at low pO 2 , 500 °C and 5.5 in oxygen content. For oxygen contents below 5.5, a larger tetragonal cell with a 3a p × 3a p × 2a p supercell is adopted [ 37 ]. Transition from a tetragonal structure to an orthorhombic structure with a later transition to the original tetragonal structure together with the oxygen content variation is shown in Figure 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Tsvetkov et al [ 36 ] reported a similar behavior for PrBaCo 2 O 5+δ where a transition from P4/mmm to Pmmm was observed at low pO 2 , 500 °C and 5.5 in oxygen content. For oxygen contents below 5.5, a larger tetragonal cell with a 3a p × 3a p × 2a p supercell is adopted [ 37 ]. Transition from a tetragonal structure to an orthorhombic structure with a later transition to the original tetragonal structure together with the oxygen content variation is shown in Figure 11 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8,22 Oxygen vacancies preferentially form on the O3-site, whereas there are indications of some oxygen vacancies in the Co-O layer. 12,15,23,24 The oxidation of oxygen vacancies on O3 sites can then be expressed as:…”
Section: Defect Chemistry Of Balnco2o6-δ Double Perovskitesmentioning
confidence: 99%
“…Among various types of TMOs, GaBaCo 2 O 5?d (GBCO) has attracted a lot of attention due to its certain interesting properties, such as insulator-metal transition (IMT) [12], total conductivity [13], charge ordering [14], magnetic transition [15] and non-stoichiometry in thermogravimetric analysis [16]. GBCO 2 ] stacked sequentially along the c axis [17].…”
Section: Introductionmentioning
confidence: 99%